Physico-chemical Studies and Thermal Decomposition Kinetics of Some Metal Complexes of Dibenzoylmethane L-Histidine - MUMTHAZ*, A.K.; PARAMESWARAN, GEETHA (Asian Journal of Chemistry, 2009)
The complexes of Co(II), Ni(II) and Cu(II) with dibenzoylmethane L-histidine (DBMH) have been synthesized and characterized on the basis of elemental analysis, molar conductance, magnetic moment, UV-visible and IR spectra. Co(II) and Ni(II) complexes of DBMH were subjected to thermal analysis so as to understand their thermal stability and decomposition patterns. The kinetic parameters like activation energy E, frequency factor A, entropy of activation ΔS and order parameter (n) were calculated from the TG curves, using Coats-Redfern equation. The mechanism of decomposition has been established from thermo-gravimetric data. On the basis of present findings the relative thermal stabilities of the chelates can be given as NiL(H2O)3 < CoL(H2O)3.